A unique case of recurrent uterine inversion requiring double reposition - Sharma, Nirmala; Ram, Kana; Sharma, Anand; Sharma, Shashi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Acute puerperal uterine inversion is a rare but life threatening complication of third stage of labour. The incidence varies widely between 1 in 2000 to 1 in 50,000 deliveries, largely dependent upon the standard of management of the third stage of labour. Acute uterine inversion occurs within 24 hours delivery; subacute between 24 hours and 4 weeks of delivery and chronic uterine inversion after 4 weeks or in the non pregnant state. Cases of subacute and chronic uterine inversion require surgical management.